Distinct role of the Port Klang Health Office as a cross-border gatekeeper in the prevention and control of communicable diseases - Xin Wee, Chen; Azhar, Zahir Izuan (Faculty of Medicine, 2023)
International ports of entry, known as ‘Pintu Masuk Antarabangsa (PMA),' have a distinct responsibility in facilitating the international trade service. Their role includes receiving and handling merchandise, clearance of travellers, collection of duties, and enforcement of import regulations. One of the most important fundamental functions of PMAs is their contribution to public health through effectively controlling the international spread of communicable diseases.